2020
DOI: 10.1029/2020tc006188
|View full text |Cite
|
Sign up to set email alerts
|

Slab Detachment, Mantle Flow, and Crustal Collision in Eastern Sicily (Southern Italy): Implications on Mount Etna Volcanism

Abstract: New data and interpretations of the geodynamics of eastern Sicily point to deep crustal shortening taking place in the area. Reconstructions of the lithospheric system, seismicity distribution, and stress state in the crust indicate that deformation is expressed by a large thrust-ramp cutting through the entire lower plate. The tectonic structure is propagating directly beneath the Mount Etna volcano, one of the few active volcanoes in Europe. Geostructural interpretation of tomographic sections allows for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 98 publications
1
29
0
Order By: Relevance
“…Noteworthy, the importance of slab tears in controlling a) convective mantle cells around slabs and b) triggering of magmatic occurrences variously influenced (or even not influenced) by subduction related fluids has been convincingly proposed by Faccenna et al (2007). Such process seems to be effective to explain the Cenozoic spatio-temporal association of volcanic products having distinct magmatic affinity in and around the Italian peninsula (e.g., Southern Tyrrhenian, Sicily; Bianchini et al, 2008;De Ritis et al, 2019;Barreca et al, 2020), as well as to explain the occurrence of post-collisional intraplate magmatism in other areas of the world, e.g., in the Western Anatolia (Dilek and Altunkaynak, 2009;Prelević et al, 2015) and East Carpathian (Bracco Gartner et al, 2020).…”
Section: Temporal and Volume Distribution Of Vvp Magmatic Activities:...mentioning
confidence: 98%
“…Noteworthy, the importance of slab tears in controlling a) convective mantle cells around slabs and b) triggering of magmatic occurrences variously influenced (or even not influenced) by subduction related fluids has been convincingly proposed by Faccenna et al (2007). Such process seems to be effective to explain the Cenozoic spatio-temporal association of volcanic products having distinct magmatic affinity in and around the Italian peninsula (e.g., Southern Tyrrhenian, Sicily; Bianchini et al, 2008;De Ritis et al, 2019;Barreca et al, 2020), as well as to explain the occurrence of post-collisional intraplate magmatism in other areas of the world, e.g., in the Western Anatolia (Dilek and Altunkaynak, 2009;Prelević et al, 2015) and East Carpathian (Bracco Gartner et al, 2020).…”
Section: Temporal and Volume Distribution Of Vvp Magmatic Activities:...mentioning
confidence: 98%
“…Recently, Barreca et al (2020) suggested the presence of a slab window in the subducting Ionian plate that allows portions of the shallow mantle wedge to flow in the opposite direction and toward Etna. Such a scenario could explain the presence of a slight subduction signature in the recent alkaline activity but not the high Nb/Ta of Etna magmas.…”
Section: Geodynamic Implicationsmentioning
confidence: 99%
“…Such a scenario could explain the presence of a slight subduction signature in the recent alkaline activity but not the high Nb/Ta of Etna magmas. In fact, the slab window opened after the tholeiitic activity of Etna (Barreca et al, 2020), which possibly explains the decreasing Nb/Ta in the younger alkaline basalts where the older carbonatite-like signature is partially overprinted. Accordingly, CO 2 and volatile fluxes at Etna during its tholeiitic phase were likely even higher than now, as suggested by the postulated increase in H 2 O/CO 2 of the mantle source of Etna through time (Casetta et al, 2019).…”
Section: Geodynamic Implicationsmentioning
confidence: 99%
“…The tectonic activity of the eastern flank of Mt. Etna must be framed within the geodynamic context of north-eastern Sicily and the western Ionian Sea, where regional processes occur [11,13,14,[23][24][25][26][27][28][29]. In particular, according to Monaco et al [30], the Timpe Fault System connects the transtensional faults characterizing the south-eastern sector of the volcano with a regional shear zone that extends offshore (the Alfeo-Etna Fault System of Polonia et al [9]; the North Alfeo Fault System of Gutscher et al [10]; Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, possible implications with volcanic activity are examined. The interpretation makes use of numerous studies already published by our research group (e.g., [2][3][4][5][9][10][11]18,22,28,30]), integrated by new seismological and marine geology data recently acquired in the offshore.…”
Section: Introductionmentioning
confidence: 99%